Applied Discrete-Time Queues - Alfa, Attahiru; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This book introduces the theoretical fundamentals for modeling queues in discrete-time, and the basic procedures for developing queuing models in discrete-time. There is a focus on applications in modern telecommunication systems. It presents how most queueing models in discrete-time can be set up as discrete-time Markov chains. Techniques such as matrix-analytic methods (MAM) that can used to analyze the resulting Markov chains are included. This book covers single node systems, tandem system and queueing networks. It shows how queues with time-varying parameters can be analyzed, and illustrates numerical issues associated with computations for the discrete-time queueing systems. Optimal control of queues is also covered. Applied Discrete-Time Queues targets researchers, advanced-level students and analysts in the field of telecommunication networks. It is suitable as a reference book and can also be used as a secondary text book in computer engineering and computer science. Examples and exercises are included.
Introduction -- Arrival and Service Processes -- Discrete-Time Markov Chains -- Numerical Computations with Discrete-Time Markov Chains -- Basic Single Node Queueing Models with Infinite Buffers -- Basic Single Node Queueing Models with Finite Buffers -- Multiserver Single Node Queueing Models -- Single Node Queuing Models with Server Vacations -- Single Node Queueing  Models with Priorities -- Special Single Node Queueing Models -- Queues with Time Varying Parameters -- Tandem Queues and Queueing Networks -- Optimization and Control of Discrete-Time Queues.
Keywords: Telecommunication; Computer networks .; Electric power production; Communications Engineering, Networks; Computer Communication Networks; Electrical Power Engineering; Microwaves, RF Engineering and Optical Communications